Kultur Sel Otak Ikan Kerapu Bebek (Cromileptes altivelis) dengan Menggunakan Media L-15, MEM Dan TCM [Cell Culture Brain Of Chromileptes altivelis With Medium L-15, MEM And TCM]. - Hari Suprapto; Nunik Diantiwi (Faculty of Fisheries and Marine Universitas Airlangga, 2010)
Abstract Humpback grouper is high value commodity fish. The demand of domestic and foreign markets increases every year. The obstacles of Humpback grouper fish cultivation is a disease caused by Viral Nervous Necrosis (VNN). The virus attacks the brain leading to mass death. To prevent the disease, a research on VNN virus has to be started. The problem of the research is the lack of culture of fish tissue. Virus have specific location to tissue cell and species to be infected. Thereofore, first step must be done is growth from tissue cell which infection of virus. Cell culture is a technique to isolate cell, protoplasm, tissue or organ to be grown in a sterile condition with nutrition containing growth hormone to promote multiplication. Cell culture technique can be used in many basic applications in cell biology. The purpose of this research is to develop cell culture from Grouper fish brain for VNN research. The hope is culture can grow and develop well.Research executed at June until Desember 2009 in Laboratory In Vitro of Veterinari Faculty of Airlangga University and Laboratory Gastroenteritis Institute of Tropical Disease, Airlangga University, Surabaya. The result showed that brain cell culture of humpback grouper fish can be grow and multiply well in all three media, media L-15 cell growth was faster compared to media MEM and TCM.